Qualitative behavior of systems of tumor–CD4+–cytokine interactions with treatments. (29th December 2014) - Anderson, Luke; Jang, Sophia; Yu, Jui‐Ling
Abstract : Immunotherapies are important methods for controlling and curing malignant tumors. Based on recent observations that many tumors have been immuno‐selected to evade recognition by the traditional cytotoxic T lymphocytes, we propose mathematical models of tumor–CD4 + –cytokine interactions to investigate the role of CD4 + on tumor regression. Treatments of either CD4 + or cytokine are applied to study their effectiveness. It is found that doses of treatments are critical in determining the fate of the tumor, and tumor cells can be eliminated completely if doses of cytokine are large. Bistability is observed in models with either of the treatment strategies, which signifies that a careful planning of the treatment strategy is necessary for achieving a satisfactory outcome. Copyright © 2014 John Wiley & Sons, Ltd.